The Value of Ecological Wisdom in the Oral Story of the Toba Batak "Tombak Sulu Sulu": An Ethnographic Study - Sihite, Ipan; Simanjuntak, Berliana; Simanungkalit, Kaleb E.; Siallagan, Dahlia Nopelina (Journal La Lifesci, 2024)
This research explores the values of ecological wisdom contained in Toba Batak's oral stories, especially the legend of "Tombak Sulu Sulu." The background of this research is based on the importance of environmental preservation amid the threat of ecological disasters around Lake Toba. The method used is qualitative, with an ethnographic study conducted in the Bakkara Valley. Data was collected through in-depth interviews with traditional leaders, field observations, and documentation related to the legend. The results showed that this legend contains five central values of ecological wisdom: respecting nature, living in harmony with nature, wise use of natural resources, using environmental knowledge for place naming (toponymy), and making nature a spiritual tool. These values emphasize the importance of harmonious relationships between humans and the environment that can be integrated into nature conservation and sustainable development efforts. This research offers a new perspective on how traditional narratives can build societal ecological awareness.